2006
DOI: 10.1079/phn2006841
|View full text |Cite
|
Sign up to set email alerts
|

Short-term daily or weekly administration of micronutrient Sprinkles™ has high compliance and does not cause iron overload in Chinese schoolchildren: a cluster-randomised trial

Abstract: The high consumption rates and appropriate SF concentrations in the supplemented groups suggest that a short-term school programme with Sprinkles is an efficient and safe way to provide micronutrients (including iron).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
1
25
1
2
Order By: Relevance
“…The lack of significant intervention effect on Hb concentration in the study was surprising. Evidence from other studies within similar age groups showed that the use of multiple micronutrient intervention led to improvement in Hb concentration in some (Lopriore et al 2004, Ayoya et al 2009) but not in all , Sharieff et al 2006, Wegmuller et al 2006. However, it is very difficult to explain the observed difference in Hb concentration in the experimental and control groups.…”
Section: Context and Fidelitymentioning
confidence: 93%
“…The lack of significant intervention effect on Hb concentration in the study was surprising. Evidence from other studies within similar age groups showed that the use of multiple micronutrient intervention led to improvement in Hb concentration in some (Lopriore et al 2004, Ayoya et al 2009) but not in all , Sharieff et al 2006, Wegmuller et al 2006. However, it is very difficult to explain the observed difference in Hb concentration in the experimental and control groups.…”
Section: Context and Fidelitymentioning
confidence: 93%
“…The final questionnaire included 254 items under sixteen sections: (1) household information; (2) child's and caregiver's demographic characteristics; (3) household assets; (4) household food security status; (5) exposure to home fortification with MNP; (6) household water and sanitation facilities; (7) food security status of the household; (8) child's morbidity; (9) child's history of taking medicine; (10) IYCF practices; (11) mother's dietary diversity; (12) household exposure to industry-fortified foods; for example, fortified salt and oil; (13) caregiver exposure to advice from an SS on home fortification with MNP; (14) nutrition status of the mother and child; (15) immunisation coverage; and (16) home visit by BRAC's SS. We asked caregivers whether the household had ever been visited by a BRAC's SS.…”
Section: Data Collectionmentioning
confidence: 99%
“…Micronutrient sachets used in research studies contain 300 μg (Sharieff and others 2006) to 400 μg VA (Menon and others 2007). The value used for this simulation was 375 μg, which is the amount contained in the sachets that were part of the Tsunami relief efforts in Indonesia (Helen Keller Intl.…”
Section: Food‐based Approaches For Ensuring Adequate Vitamin a Nutritionmentioning
confidence: 99%
“…The objectives of this review were, first, to summarize studies with animals and humans fed provitamin A sources and then to apply this study to models to predict changes in liver VA concentrations of preschool and adolescent children after various VA interventions. The 1st evaluation compared potential increases in VA liver reserves of a model infant fed micronutrient tablets (Nestel and others 2003) or sachets such as “Sprinkles” (Sharieff and others 2006; Sprinkles Global Health Initiative 2007) with a daily serving of orange‐fleshed sweet potato (van Jaarsveld and others 2005). The 2nd evaluation determined the change in liver VA concentration in a boy, 1 to 4 y old, who had eaten biofortified maize, received twice yearly 200000 IU supplements, or consumed fortified sugar for a 3‐y period.…”
Section: Introductionmentioning
confidence: 99%